Investigation of corrosion effects on aluminum-stainless steel weld joint - Nurul Asmida, Kamaruddin (2012)
In this study, effect of changing welding parameters on microstructure, mechanical properties and corrosion rate was investigated. Aluminum alloy AA6061 joined stainless steel AISI304 with same thickness of 2 mm welded using automatic MIG welding with filler metal ER5356 where arc current and arc voltage were chosen as variable parameters. Microstructure of welded area was studied using metallurgy microscope, mechanical properties observed by Vickers hardness and corrosion rate determined in artificial corrosion test with seawater aqueous solution. Results indicated that weld metal consist Al-Si in dendritic structure and formation brittle intermetallic compound at interface aluminum alloy-stainless steel. Weld metal performed with finer microstructure and heat affected zone (HAZ) in coarse grain structure. Black surface and pitting formed after corrosion. Minimum hardness was found at fusion zone of weld metal and after corrosion hardness slightly decreased due to the pitting corrosion. Corrosion rate was determined by potentiodynamic polarization curves. Sample which has lower corrosion rate means better corrosion resistance. The optimum parameters were 93A current and 13.5V voltage.